Crisis of Parental Conflict: Impact on Children and Families - Vandana Nangia (Jesuit University Ignatianum in Krakow, 2023)
RESEARCH OBJECTIVE: This article explores the impact of parental conflict crises on children and families, focusing on the traumatic situations caused by recurrent disagreements. These crises generate unease, worry, and perplexity, compromising emotional regulation and social abilities. They can lead to behavioural problems and academic underachievement, as they compromise emotional regulation and social abilities. The article aims to understand the complexities of these situations and their potential consequences for children and families. THE RESEARCH PROBLEM AND METHOD: The study investigates the impact of parental conflict on children's emotional, psychological, and relational well-being. It employs a detailed assessment of reference material, self-reporting, and direct observation methodologies to understand the negative effects on children's performance. THE PROCESS OF ARGUMENTATION: After discussing the impact of domestic conflicts on children's self-esteem, the presentation moved on to cognitive and emotional dysregulation, the relationship between resilience, risk, and crisis, the need to develop persistence and the influence of cultural values in the development of such perseverance, gender concerns, and early intervention. RESEARCH RESULTS: Conflicting parents have a substantial impact on a child's subjective well-being. Prolonged stress can lead to sleep disorders, reduced immune systems, and chronic health problems. Prolonged disagreements can impact relationships, boundaries, and emotional control well into adulthood. CONCLUSION, RECOMMENDATION AND APPLICABLE VALUE OF RESEARCH: Parental disagreements require interventions at various levels, including counseling, therapy, mediation services, and a holistic approach. Counseling and therapy help children process feelings and strengthen coping skills, while mediation guides parents through separation or divorce processes, prioritizing their children's best interests and maintaining stable family dynamics and good childhoods.